BPIQ, a novel synthetic quinoline derivative, inhibits growth and induces mitochondrial apoptosis of lung cancer cells in vitro and in zebrafish xenograft model. Issue 1 (December 2015) - Chiu, Chien-Chih; Chou, Han-Lin; Chen, Bing-Hung; Chang, Kuo-Feng; Tseng, Chih-Hua; Fong, Yao; Fu, Tzu-Fun; Chang, Hsueh-Wei; Wu, Chang-Yi; Tsai, Eing-Mei; Lin, Shinne-Ren; Chen, Yeh-Long
Abstract Background 2, 9-Bis[2-(pyrrolidin-1-yl)ethoxy]-6-4-[2-(pyrrolidin-1-yl)ethoxy] phenyl-11H -indeno[1, 2-c ]quinolin-11-one (BPIQ) is a derivative from 6-arylindeno[1, 2-c ]quinoline. Our previous study showed the anti-cancer potential of BPIQ compared to its two analogues topotecan and irinotecan. In the study, the aim is to investigate the potency and the mechanism of BPIQ against lung cancer cells. Methods Bothin vitro and zebrafish xenograft model were performed to examine the anti-lung cancer effect of BPIQ. Flow cytometer-based assays were performed for detecting apoptosis and cell cycle distribution. Western blot assay was used for detecting the changes of apoptotic and cell cycle-associated proteins. siRNA knockdown assay was performed for confirming the apoptotic role of Bim. Results Bothin vitro and zebrafish xenograft model demonstrated the anti-lung cancer effect of BPIQ. BPIQ-induced proliferative inhibition of H1299 cells was achieved through the induction of G2 /M-phase arrest and apoptosis. The results of Western blot showed that BPIQ-induced G2 /M-phase arrest was associated with a marked decrease in the protein levels of cyclin B and cyclin-dependent kinase 1 (CDK1). The up-regulation of pro-apoptotic Bad, Bim and down-regulation of pro-survival XIAP and survivin was observed following BPIQ treatment. Conclusions BPIQ-induced anti-lung cancer is involved in mitochondrial apoptosis. BPIQ could be a promising anti-lung cancer drug for further applications.